2006
DOI: 10.1159/000096825
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Mechanisms Involved in Prolactin Release after Mifepristone and Naloxone Treatment during Late Pregnancy in the Rat

Abstract: Background/Aims: During late pregnancy, the antiprogesterone mifepristone facilitates prolactin release. This effect is enhanced by administration of the opioid antagonist naloxone, suggesting an inhibitory-neuromodulatory role of the opioid system. Since hypothalamic dopamine (DA) is the main regulator of prolactin release, in this study we explored the role of DA on prolactin release induced by mifepristone and naloxone treatment. Methods/Results: Rats on day 19 of pregnancy were used. Naloxone treatment did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 119 publications
(93 reference statements)
2
19
0
Order By: Relevance
“…Moreover, it seems that naloxone treatment activates these neurons as well, suggesting an additional pathway by which endogenous opioids may regulate prolactin secretion. Although, at the end of pregnancy there is no evidence of the participation of this neuronal system to control prolactin secretion, the results above may support our recent study [12] which demonstrates that during late pregnancy, naloxone treatment has no direct effect on dopaminergic neurons, either in control oil-treated rats or in mifepristone-pretreated rats. Thus, endogenous opioids may inhibit prolactin secretion during late pregnancy through a nondopaminergic neuronal system without involvement of a direct effect on neuronal DA activity and probably with the participation of as yet undetermined prolactin-releasing factors unmasked by naloxone treatment.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Moreover, it seems that naloxone treatment activates these neurons as well, suggesting an additional pathway by which endogenous opioids may regulate prolactin secretion. Although, at the end of pregnancy there is no evidence of the participation of this neuronal system to control prolactin secretion, the results above may support our recent study [12] which demonstrates that during late pregnancy, naloxone treatment has no direct effect on dopaminergic neurons, either in control oil-treated rats or in mifepristone-pretreated rats. Thus, endogenous opioids may inhibit prolactin secretion during late pregnancy through a nondopaminergic neuronal system without involvement of a direct effect on neuronal DA activity and probably with the participation of as yet undetermined prolactin-releasing factors unmasked by naloxone treatment.…”
Section: Introductionsupporting
confidence: 64%
“…In fact, we have recently demonstrated that mifepristone treatment to rats on day 19 of pregnancy induced a fall in the DOPAC/DA ratio in MBH, a diminution of the expression of TH measured in protein extracts of MBH as well as a decrease in the intensity of TH immunoreactivity in the arcuate nuclei, periventricular nuclei and the nerve terminals of the median eminence [12]. These results complement and confirm previous work showing that progesterone increases hypothalamic dopaminergic tone and TH expression [24, 25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, oestradiol preferentially upregulates PR-B as compared to PR-A expression in the hypothalamus (54) and the increased PR-B to PR-A ratio may contribute to the progesterone stimulatory effect. Although sparsely explored, a stimulatory effect for progesterone during late pregnancy is suggested by the ability of RU486 treatment to decrease TH protein levels in the medial basal hypothalamus (55). In contrast to its stimulatory action, progesterone can also have an inhibitory effect on the tuberoinfundibular dopaminergic neurons with a decrease in TH activity, TH phosphorylation levels and TH mRNA levels in tuberoinfundibular dopamine neurons observed on the evening of prooestrus, but RU486 treatment on pro-oestrus had no effect on the progesterone induced suppression of TH mRNA levels (6,(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneous fall in P 4 provoked by luteolysis at the end of pregnancy, or induced by ovariectomy, luteectomy or prostaglandin F2α (PGF2α)-induced luteolysis triggers a surge of PRL 12–24 h later that has been extensively studied in our laboratory [5,23,24,25,26,27], but little information is available on the changes in hypothalamic PRL regulatory mechanisms after the P 4 decline, in particular whether this decline produces changes in TH, ER, P 4 (PR), PRLR and some proteins involved in PRL signaling (STAT5 and SOCS family members) expression, all factors that may play a role in triggering PRL release. With the aim of investigating if the P 4 fall induces changes in hypothalamic dopaminergic activity and in the expression of receptors that regulate the dopaminergic neurons, we have determined the expression of TH, receptors for PRL (long form, PRLR long ), estrogen (ER) α and β, P 4 (PRA and B), STAT5a, STAT5b, SOCS1, SOCS3 and CIS, and DA and its metabolite DOPAC contents in the mediobasal hypothalamus (MBH) on day 20 of pregnancy, 24 h after PGF2α-induced luteolysis.…”
Section: Introductionmentioning
confidence: 99%